1988
DOI: 10.5144/0256-4947.1988.261
|View full text |Cite
|
Sign up to set email alerts
|

Urinary Tract Infection at a University Hospital in Saudi Arabia: Incidence, Microbiology, and Antimicrobial Susceptibility

Abstract: Midstream and catheter stream specimens of urine from inpatients and outpatients at King Abdulaziz University Hospital in Jeddah, Saudi Arabia, were collected over a period of 12 months to determine prospectively the incidence of urinary tract infection, the predominant causative organisms, and their antimicrobial susceptibility. A total of 575 of 9845 specimens (5.8%) showed significant bacteriuria. The overall prevalence of urinary tract infection was 12.1%, 7.4% in inpatients and 4.7% in outpatients. Infect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
15
2

Year Published

1989
1989
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 9 publications
6
15
2
Order By: Relevance
“…Other studies have reported similar findings. 3,4,11,12 The most frequent gram-positive isolates in our study were streptococci, which also agrees with the findings of other investigators. 4,6,8 However, Scheckler 3 reported that Staphylococcus aureus was the most frequent gram-positive isolate in patients with communityacquired bacteremia in his series.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Other studies have reported similar findings. 3,4,11,12 The most frequent gram-positive isolates in our study were streptococci, which also agrees with the findings of other investigators. 4,6,8 However, Scheckler 3 reported that Staphylococcus aureus was the most frequent gram-positive isolate in patients with communityacquired bacteremia in his series.…”
Section: Discussionsupporting
confidence: 83%
“…This agrees with other studies. 3,11 Weinstein et al 5 and Macfarlane and Narla 8 identified the respiratory tract as the most frequent site of origin, and this was the second most frequent source of infection in our series. The origin of Brucella bacteremia could not be documented clinically or microbiologically.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…1,2 An incidence of 7/1000 hospital admissions has been reported from Abu Dhabi, 1 10.9/1000 from Kuwait, 3 and 13.5/1000 in Saudi Arabia. 4 Incidence reported from the United States and Europe has ranged from 3.4 to 28/1000 hospital-admissions, 5 and Nigeria has reported a higher incidence approaching 37/1000 hospital admissions. 6 Studies from developed countries showed clear predominance of hospital-acquired bacteremia.…”
mentioning
confidence: 99%
“…To the Editor: In recent articles [1,2], various microorganisms responsible for urinary tract infections from hospitals in Saudi Arabia were reported. The most frequently isolated etiological agents of urinary tract infections with Escherichia coli, Klebsiella-Enterobacter group and Pseudomonas sp.…”
mentioning
confidence: 99%